2011
DOI: 10.1093/eurheartj/ehq496
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial translocation of Nur77 mediates cardiomyocyte apoptosis

Abstract: Translocation of Nur77 from the nucleus to the mitochondria in cardiomyocytes results in the loss of mitochondrial integrity and subsequent apoptosis in response to ischaemia/reperfusion injury. Our findings identify Nur77 as a novel mediator of cardiomyocyte apoptosis and warrants further investigation of mitochondrial Nur77 translocation as a mechanism to control cell death in the treatment of ischaemic heart diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 43 publications
4
74
1
Order By: Relevance
“…Given these results, it is possible that cardiac NR4A1 is activated in the heart under stress conditions such as adrenergic stimulation to regulate metabolism as a stress response. However, other studies have demonstrated that NR4A1 exits the nucleus and translocates to the mitochondria to facilitate cytochrome C release and stimulate apoptosis (43). In support of this model, loss of NR4A1 protects the heart from angiotensin II-induced cardiac hypertrophy (44).…”
Section: Control Of Cardiac Fuel Metabolism By Other Nuclear Receptorsmentioning
confidence: 90%
“…Given these results, it is possible that cardiac NR4A1 is activated in the heart under stress conditions such as adrenergic stimulation to regulate metabolism as a stress response. However, other studies have demonstrated that NR4A1 exits the nucleus and translocates to the mitochondria to facilitate cytochrome C release and stimulate apoptosis (43). In support of this model, loss of NR4A1 protects the heart from angiotensin II-induced cardiac hypertrophy (44).…”
Section: Control Of Cardiac Fuel Metabolism By Other Nuclear Receptorsmentioning
confidence: 90%
“…and cardiac ischemia/reperfusion injury). [8][9][10] In VSMCs, Nur77 can be induced by multiple stimuli, including cytokines, growth factors, oxidized low-density lipoprotein, and vascular injury. 11,25,26 We found that Nur77 was highly expressed in medial VSMCs of thoracic aortas from Ang II-infused mice in vivo and in cultured VSMCs after Ang II stimulation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that NR4A receptors play essential roles in the development of atherosclerosis, restenosis, and angiogenesis (17,18,33). However, the functional role of the NR4A receptor in cardiomyocyte biology remains largely obscured, although several studies suggest that the NR4A receptors are highly expressed in the heart and that their expression is regulated by several external pathological stimuli, such as oxidative stress, pressure overload, and ␤-AR activation (19,20,34). In the present study, we sought to examine the role of Nur77 in cardiac hypertrophy and found that the expression of Nur77 is substantially increased in response to a wide range of hypertrophic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, our recent study has implicated Nur77 as a potent negative regulator for the proinflammatory response in ECs via a selective inhibition of NF-B activation (18). In cardiomyocytes, Nur77 expression can be induced by ischemia/reperfusion injury, and translocation of Nur77 to the mitochondria mediates cardiomyocyte apoptosis in response to oxidative stress (19). Interestingly, a recent report demonstrated that the expression of Nur77 in the heart was rapidly induced in vivo following ␤-adrenergic stimulation (20,21).…”
mentioning
confidence: 98%